2015
DOI: 10.12669/pjms.312.6530
|View full text |Cite
|
Sign up to set email alerts
|

Adverse fetomaternal outcome among pregnant overweight women

Abstract: Objective:To compare the adverse fetometernal out come in overweight and normal weight pregnant women.Methods:This comparative cohort study was conducted from 1st October 2010 to 30 September 2012. Total 200 gravid women 100 were overweight and 100 normal weight pregnant women with gestational age for 08-40 weeks were included. Women having BMI (25 – 29.9 Kg/m2) were measured overweight and included in group A and 100 women having normal BMI of 18.5 to 24.9 as controls were in-group B. Chi-square test was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…P<0.003 which was stastically significant. This was similar to that reflected by Awan et al [36] study in which 27% of overweight/obese pregnant mothers developed pre eclampsia, p< 0.009.  The incidence of GDM in overweight/obese group 2.7% of mothers, & in normal weight group, 1.3%, p> 0.011 statistically insignificant.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…P<0.003 which was stastically significant. This was similar to that reflected by Awan et al [36] study in which 27% of overweight/obese pregnant mothers developed pre eclampsia, p< 0.009.  The incidence of GDM in overweight/obese group 2.7% of mothers, & in normal weight group, 1.3%, p> 0.011 statistically insignificant.…”
Section: Introductionsupporting
confidence: 92%
“… 25.3% of mothers in overweight/obese group had PROM, 9.3% of patients in the normal weight group had PROM, p< 0.001 statistically significant. In a similar study Awan et al [36] [41] he studied the normal and obese population a total of 29, 224 women with singleton pregnancies between 2004 and 2008 of whom induction of labour of normal weight mothers was 42.26% and obese group mothers was 52.11% which was significant with p< 0.001. In a similar study by Awan et al [36] revealed in which 26.7% of overweight/obese pregnant mothers required Induction of labor p< 0.001.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…An important factor that helped in the successful outcome in this lady was that the indication of first cesarean section was not a recurrent cause (breech presentation, unless the breech recurred), also the patient was young and of normal body mass index. Body mass index greater than 30 is a predictor of unsuccessful outcome (14) . Advanced maternal age is associated with decreased likelihood of planned vaginal birth after cesarean success (15) .…”
Section: Discussionmentioning
confidence: 99%
“…The sedentary lifestyle adopted by many pregnant women predisposes them to obesity, hypertension or gestational diabetes mellitus (GDM) [ 5 , 6 , 8 ], and the physiological changes occurring during gestation magnify this risk [ 9 ]. Importantly, overweight or obesity during pregnancy is associated with a significantly higher risk of pre-term delivery [ 10 ], birth-asphyxia-related complications [ 11 ], pre-eclampsia, GDM, prolonged labour, caesarean section, wound infection, postpartum haemorrhage, early neonatal death or neonatal intensive care admission [ 12 15 ], and infant mortality [ 16 ].…”
Section: Introductionmentioning
confidence: 99%